New specimen of an Early Iron Age brooch type from Western Transdanubia - Gábor Ilon (Dissertationes Archaeologicae: Ex Instituto Archaeologico Universitatis de Rolando Eötvös Nominatae)
The museum obtained the two-loop nodular (or knobbed) bow brooch, a stray find, in 1970. The jewellery, 66 mm long and weighing 22.6 g, is still in good condition today. Its shape is a mixture of Types 6a and 6d in Stane Gabrovec’s system, which were in vogue in the Ha C1–2 phases, i.e., from the mid-8th to the mid-7th centuries BC. In lack of a find context and accompanying finds, the artefact in focus cannot be dated more precisely within this period; the topographical position of its findspot fills an empty area in the foregrounds of the Eastern Alps.